PENGARUH KETINGGIAN TEMPAT TERHADAP SIFAT FISIOLOGI DAN HASIL KOPI ARABIKA (Coffea arabica) DI DATARAN TINGGI DESA SARWODADI KECAMATAN PEJAWARAN KABUPATEN BANJARNEGARA - Purwanto (Unit Penelitian dan Pengabdian Masyarakat (UP2M) Politeknik Banjarnegara, 2021)
Coffee is a plantation commodity that is on the rise in line with the increasing demand for coffee both domestically and abroad. The quality of Arabica coffee is greatly affected by the management of cultivation techniques and altitude. Pejawaran District is an area that has developed Arabica coffee, however, plant management is not optimal so that productivity is low. This research was conducted in Sarwodadi Village, Pejawaran District, Banjarnegara Regency from July to September 2019. Data collection was carried out by survey method at 4 locations with different altitudes namely 800, 1.000, 1.250 and 1.400 m asl. The samples were taken by 10 percent from total population of population . The observation variables included plant height, number of beans per bag, yield of dry coffee beans per plant, weight per seed, density of stomata, width of stomatal opening and leaf chlorophyll content. The cultivation performance in Sarwodadi Village was very diverse and was not in accordance with good coffee cultivation, the farmers only take the results without carrying out optimal care as recommended. The highest seed yields were achieved at 1.250 m asl of 6,04 kg / plant, as well as the physiological characters which included stomata density 191,68 units/mm2 and stomata opening width of 3,28 µm. Key words: arabica, coffee, cultivation, high land